2017
DOI: 10.1016/j.radcr.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal carcinomatosis and bilateral internal auditory canal metastases from ovarian carcinoma

Abstract: Ovarian cancer, a leading cause of death in women, typically spreads locally and rarely metastasizes to the brain or seeds the leptomeninges. We present a case of a 62-year-old woman with a history of treated ovarian cell carcinoma who developed bilateral sensorineural deafness and right-sided facial weakness and on imaging was found to have bilateral internal auditory canal (IAC) masses and leptomeningeal carcinomatosis, pathologically proven by cerebrospinal fluid cytology. We discuss her magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…A systematic review of the literature revealed 30 publications that met criteria for cases of leptomeningeal carcinomatosis in ovarian carcinoma, and a total of 32 patients were included ( 5 , 11 , 20 – 47 ). The median time to leptomeningeal carcinomatosis from ovarian carcinoma diagnosis was 24 months, and 41% of patients had brain or spine metastases present before or at the time of leptomeningeal carcinomatosis diagnosis.…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review of the literature revealed 30 publications that met criteria for cases of leptomeningeal carcinomatosis in ovarian carcinoma, and a total of 32 patients were included ( 5 , 11 , 20 – 47 ). The median time to leptomeningeal carcinomatosis from ovarian carcinoma diagnosis was 24 months, and 41% of patients had brain or spine metastases present before or at the time of leptomeningeal carcinomatosis diagnosis.…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
“…As such, the literature on the natural history and effective treatment strategies of this phenomenon remains sparse. Krupa et al ( 5 ) reported a 62-year-old female with stage IIC high-grade serous ovarian carcinoma with malignant ascites but without involvement of lymph nodes who underwent bilateral salpino-oophorectomy, omentectomy, and adjuvant chemotherapy. She presented approximately one year thereafter with rapidly progressive bilateral sensorineural hearing loss, right-sided facial paralysis, gait instability, and radicular low back pain in conjunction with a marked rise in her CA-125 level ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations